2017
DOI: 10.1002/jmri.25914
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tendon assessment using magic‐angle insensitive 3D ultrashort echo time cones magnetization transfer (UTE‐Cones‐MT) imaging and modeling with histological correlation

Abstract: Background: Rotator cuff tendons (RCTs) are challenging to image due to the "magic angle effect" and their short T 2 . Purpose: To assess the degree of magic angle sensitivity of human RCTs and to utilize a 3D ultrashort echo time Cones sequence with magnetization transfer preparation (UTE-Cones-MT) and two-pool quantitative MT modeling with histological correlation. We hypothesized that MT parameters would be less sensitive to the magic angle compared with conventional T 2 measurements. Study Type: Prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 35 publications
3
60
2
Order By: Relevance
“…Magnetization transfer (MT) modeling combined with UTE-MRI has recently been used to indirectly measure the macromolecular protons fraction (MMF) in different tissues 20,21,23–28 . Interestingly, two-pool UTE-MT modeling has demonstrated promise as a clinically compatible quantitative technique that is resistant to the magic angle effect 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Magnetization transfer (MT) modeling combined with UTE-MRI has recently been used to indirectly measure the macromolecular protons fraction (MMF) in different tissues 20,21,23–28 . Interestingly, two-pool UTE-MT modeling has demonstrated promise as a clinically compatible quantitative technique that is resistant to the magic angle effect 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetization transfer (MT) modeling combined with UTE-MRI has recently been used to indirectly measure the macromolecular protons fraction (MMF) in different tissues 20,21,23–28 . Interestingly, two-pool UTE-MT modeling has demonstrated promise as a clinically compatible quantitative technique that is resistant to the magic angle effect 20,21 . Specifically, UTE-MT modeling has been recently implemented on cadaveric Achilles and rotator cuff tendons in order to assess MMF, and showed roughly no orientation angle sensitivity 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies using the UTE MT technique on rotator cuff tendons have shown promising results that are much less sensitive to magic angle effects compared with transverse relaxation times [103,104] (Fig. 6).…”
Section: Ultrashort-te Magnetization Transfermentioning
confidence: 99%